2012
DOI: 10.1111/j.1365-2559.2012.04203.x
|View full text |Cite
|
Sign up to set email alerts
|

Activating PDGFRA mutations in inflammatory fibroid polyps occur in exons 12, 14 and 18 and are associated with tumour localization

Abstract: We conclude that there is a 'small bowel' and a 'gastric' phenotype of IFPs which are associated with exon 12 and exon 18 PDGFRA mutations, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 20 publications
3
71
0
4
Order By: Relevance
“…5,6 PDGFRA exon-14 mutations occur in o 1% of GISTs 26 and, to the best of our knowledge, have very rarely been reported in inflammatory fibroid polyps. 27 P653L PDGFRA mutation is hitherto unreported. 28 Highly conserved amino acid alignment of tyrosine kinase I PDGFRA and KIT domains shows correspondence between codon 653 of PDGFRA and codon 649 of KIT (exon 13), whose substitutions have also never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 PDGFRA exon-14 mutations occur in o 1% of GISTs 26 and, to the best of our knowledge, have very rarely been reported in inflammatory fibroid polyps. 27 P653L PDGFRA mutation is hitherto unreported. 28 Highly conserved amino acid alignment of tyrosine kinase I PDGFRA and KIT domains shows correspondence between codon 653 of PDGFRA and codon 649 of KIT (exon 13), whose substitutions have also never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…11 Accordingly, the reported gallbladder tumor would belong to the ''gastric'' type of IFPs; however, considering the specific PDGFRA mutation instead of the exon harboring it, it is noteworthy that the only IFP with a PDGFRA del D842 reported before the one described in this study was actually found in the small bowel, namely in the duodenum. 12 Thus, in a perspective of possible site-specific PDGFRA mutations of IFPs, it seems conceivable that the present gallbladder case is more akin to a comparatively unusual intestinal-type of IFP bearing the PDGFRA exon 18 mutation del D842 than to the ''gastric'' IFP family sharing a PDGFRA exon 18 mutation in a broad sense.…”
Section: Commentmentioning
confidence: 64%
“…The frequency of mutations ranges from 21% to 69%. 5,6 In the gastric type of IFP, spindle cells are positive for CD 34. However in the intestinal type this is not seen.…”
Section: Genetics and Immunohistochemistrymentioning
confidence: 99%